De novo genome hybrid assembly and annotation of the endangered and euryhaline fish Aphanius iberus (Valenciennes, 1846) with identification of genes potentially involved in salinity adaptation - Alfonso López-Solano; Ignacio Doadrio; Tessa Lynn Nester; Silvia Perea (BMC Genomics)
Abstract Background The sequencing of non-model species has increased exponentially in recent years, largely due to the advent of novel sequencing technologies. In this study, we construct the Reference Genome of the Spanish toothcarp (Aphanius iberus (Valenciennes, 1846)), a renowned euryhaline fish species. This species is native to the marshes along the Mediterranean coast of Spain and has been threatened with extinction as a result of habitat modification caused by urbanization, agriculture, and its popularity among aquarium hobbyists since the mid-twentieth century. It is also one of the first Reference Genome for Euro-Asian species within the globally distributed order Cyprinodontiformes. Additionally, this effort aims to enhance our comprehension of the species' evolutionary ecology and history, particularly its remarkable adaptations that enable it to thrive in diverse and constantly changing inland aquatic environments. Results A hybrid assembly approach was employed, integrating PacBio long-read sequencing with Illumina short-read data. In addition to the assembly, an extensive functional annotation of the genome is provided by using AUGUSTUS, and two different approaches (InterProScan and Sma3s). The genome size (1.15 Gb) is consistent with that of the most closely related species, and its quality and completeness, as assessed with various methods, exceeded the suggested minimum thresholds, thus confirming the robustness of the assembly. When conducting an orthology analysis, it was observed that nearly all genes were grouped in orthogroups that included genes of genetically similar species. GO Term annotation revealed, among others, categories related with salinity regulation processes (ion transport, transmembrane transport, membrane related terms or calcium ion binding). Conclusions The integration of genomic data with predicted genes presents future research opportunities across multiple disciplines, such as physiology, reproduction, disease, and opens up new avenues for future studies in comparative genomic studies. Of particular interest is the investigation of genes potentially associated with salinity adaptation, as identified in this study. Overall, this study contributes to the growing database of Reference Genomes, provides valuable information that enhances the knowledge within the order Cyprinodontiformes, and aids in improving the conservation status of threatened species by facilitating a better understanding of their behavior in nature and optimizing resource allocation towards their preservation.